Analisis Indikator INA-CBGs dalam Perencanaan Strategis Kinerja Rumah Sakit Karya Dharma Husada Singaraja - Suandewi, Dewa Ayu Sri Agung; Hendriana, Heris; Andikarya, Oke (LPPM Institut Pendidikan Nusantara Global, 2026)
Strategic planning plays a crucial role for hospitals in maintaining sustainability and competitiveness amid the dynamic healthcare environment and the National Health Insurance (JKN) financing system. The implementation of the prospective payment system based on Indonesian Case Based Groups (INA-CBGs) requires performance indicators that adequately reflect service volume, case complexity, and hospitals’ financial implications. INA-CBGs–based indicators, namely Casemix (CM), Casemix Index (CMI), and Hospital Base Rate (HBR), have the potential to support performance assessment and strategic planning; however, their utilization in private hospitals remains limited. This study aims to analyze the performance achievement of INA-CBGs indicators and examine their relevance for strategic performance planning at Karya Dharma Husada Hospital (RS KDH) Singaraja. This study employed a mixed methods approach with a sequential explanatory design. Quantitative analysis was conducted longitudinally using a trend study approach on inpatient INA-CBGs claim data from 2022 to January–June 2024, followed by qualitative analysis through in-depth interviews to interpret and contextualize the quantitative findings. The results showed a total of 7,361 inpatient JKN cases, predominantly involving class III patients and low-severity cases. Casemix values fluctuated in line with changes in service volume and case mix, with obstetric cases being the dominant contributor. CMI values remained within the typical range for private class C hospitals, reflecting low to moderate service complexity. HBR performance demonstrated periods of surplus and deficit, indicating discrepancies between actual service costs and national INA-CBGs tariffs. Overall, the study indicates that INA-CBGs indicators have not yet been systematically integrated into performance evaluation and strategic planning; however, hospital management has recognized them as valuable information with potential to support future managerial decision-making.